(untitled) (New York, NY, 2002)
this two volume encyclopedia set provides a preface defining what is meant by and summarizing their enormous potential: tiny sensory computers, some no larger than a dust mote, will someday fundamentally impact a multitude of industries, products, and human activities. In two volumes, in-depth articles on various aspects of this multidisciplinary field are arranged alphabetically and include substantial bibliographies; there are no cross-references, but thematic access is afforded by the subject index in the second volume
Keywords: Smart materials; Encyclopedias